2017
DOI: 10.3389/fpsyg.2016.02007
|View full text |Cite
|
Sign up to set email alerts
|

Large Group Exposure Treatment: A Feasibility Study of Exposure Combined with Diaphragmatic Breathing in Highly Dental Fearful Individuals

Abstract: A large-group one session treatment (LG-OST) combining exposure and diaphragmatic breathing as a bodily coping element was carried out to investigate its feasibility and effectiveness in a sample of 43 highly dental fearful individuals treated simultaneously. We assessed subjective dental fear, dysfunctional dental-related beliefs, and perceived control pre- and post-intervention and at four-month follow-up. Participants additionally performed a behavioural approach test (BAT) pre- and post-intervention. Durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 47 publications
3
13
0
Order By: Relevance
“…Our successful translation of individual to large group OST using direct exposure is consistent with Wannemueller et al's (, , ) studies, which found that exposure tasks modelled to large groups ( N = 40+) was effective in reducing fear, demonstrating that various formats of OST (direct or indirect exposure) are adaptable to large group delivery. While the group size in the current study may be considered modest compared to Wannemueller et al's studies (in which exposure to the feared stimuli was observational), they are the largest group size evaluated for treatments involving direct exposure and interaction with the feared stimuli (twice the size of Öst et al's (, 1997) original group evaluations).…”
Section: Discussionsupporting
confidence: 87%
“…Our successful translation of individual to large group OST using direct exposure is consistent with Wannemueller et al's (, , ) studies, which found that exposure tasks modelled to large groups ( N = 40+) was effective in reducing fear, demonstrating that various formats of OST (direct or indirect exposure) are adaptable to large group delivery. While the group size in the current study may be considered modest compared to Wannemueller et al's studies (in which exposure to the feared stimuli was observational), they are the largest group size evaluated for treatments involving direct exposure and interaction with the feared stimuli (twice the size of Öst et al's (, 1997) original group evaluations).…”
Section: Discussionsupporting
confidence: 87%
“…In the Phase I study, we investigated the feasibility and effectiveness of the LG-OST protocol in a group of 40 participants and explored potential outcome-predictors of LG-OST. We hypothesized that the LG-OST would lead to a substantial reduction in BII-fear, analogous to the results observed in the spider- and dental-fear cohort ( Wannemueller et al, 2016 , 2017 ). Prior to treatment, we assessed trait anxiety as a potential outcome predictor, as trait anxiety has been identified to influence treatment outcome (e.g., Muris et al, 1998 ).…”
Section: Introductionmentioning
confidence: 72%
“…Encouraged by the positive reports of small group OSTs, Wannemueller et al (2016 , 2017 ) recently conducted two Phase I open trials applying one-session formats in large-group settings (LG-OSTs). LG-OST proved feasible in a sample of N = 78 spider fearful individuals as well as in a sample of N = 43 dental fearful individuals.…”
Section: Introductionmentioning
confidence: 99%
“…However, we did not apply fixed cut-off scores which in case of falling short would have led to exclusion. Nevertheless, mean scores of specific fear questionnaires applied to all cohorts were comparable to those reported in high fear cohorts or cohorts of individuals diagnosed with a specific phobia [for a more detailed description, see 32,33].…”
Section: Participants and Treatmentmentioning
confidence: 88%
“…During the individual 1-session treatments the very same contents (video clips, etc.) as in the large-group settings were administered by the same clinical psychologists for exactly the same length [for further information concerning the contents of treatments, see 32,33]. Because 8 participants (3.6% of total; 3LL/3LS/2SS) reported to take selective serotonin reuptake inhibitors or serotonin-norepinephrine reuptake inhibitors, they were excluded from our genotype comparisons.…”
Section: Participants and Treatmentmentioning
confidence: 99%